If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5w+9=9
We move all terms to the left:
5w+9-(9)=0
We add all the numbers together, and all the variables
5w=0
w=0/5
w=0
| 43=|y-8| | | 10+7h=3 | | 3=7h+10 | | 2k+-7=-3 | | A=20w+40 | | 5w+9=9 | | A=20w+40 | | 9^x-6^x=4^x | | -2.6x=-3.5(-x-6)-6x | | -2.6x=-3.5(-x-6)-6x | | 1/3y-6=-66-2/3y | | 1/3y-6=-66-2/3y | | 1/3y-6=-66-2/3y | | 1/3y-6=-66-2/3y | | 1/3y-6=-66-2/3y | | 1/3y-6=-66-2/3y | | 1/3y-6=-66-2/3y | | 1/3y-6=-66-2/3y | | 1/3y-6=-66-2/3y | | 13x+1=53 | | G(2)=-4x2-3 | | G(2)=-4x2-3 | | 13x+1=53 | | 14p+16=44 | | 14p+16=44 | | Y=-1/2x+15/6 | | Y=-1/2x+15/6 | | Y=-1/2x+15/6 | | 12x-5=8x+23 | | 2/3x+1/6=5/2 | | 2/3x+1/6=5/2 | | 2/3x+1/6=5/2 |